ChemInform Abstract: Triphenylamines and 1, 3, 4‐Oxadiazoles: A Versatile Combination for Controlling the Charge Balance in Organic Electronics. Issue 30 (29th July 2014) - Dumur, Frederic; Goubard, Fabrice
Abstract Review: [66 refs.